2022
DOI: 10.3390/plants11111486
|View full text |Cite
|
Sign up to set email alerts
|

Antiphotoaging Effects of Damiana (Turnera diffusa) Leaves Extract via Regulation AP-1 and Nrf2/ARE Signaling Pathways

Abstract: Damiana (Turnera diffusa), of the family Passifloraceae, has been widely studied for its pharmacological effects, especially for antioxidant and antibacterial actions. However, there are limited scientific findings describing its antiphotoaging effects on the skin. In the present study, the underlying molecular mechanisms of the protective effect of Damiana were investigated in keratinocytes (HaCaTs) and normal human dermal fibroblasts (HDFs) subject to UVB irradiation. The mRNA expression of matrix metallopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…According to our comparison of the experimental results, the flavonoid contents of R. davurica bud and leaf extracts had no significant differences based on planting interval and harvest date. Kim et al's study observed that the flavonoid content of Turnera diffusa leaves was 108.8 mg QE/g extract [20]. Furthermore, Quyen et al observed that the polyphenol content of Centella asiatica ranged between 2.14 and 2.82 mg GAE/g extract [21].…”
Section: Discussionmentioning
confidence: 98%
“…According to our comparison of the experimental results, the flavonoid contents of R. davurica bud and leaf extracts had no significant differences based on planting interval and harvest date. Kim et al's study observed that the flavonoid content of Turnera diffusa leaves was 108.8 mg QE/g extract [20]. Furthermore, Quyen et al observed that the polyphenol content of Centella asiatica ranged between 2.14 and 2.82 mg GAE/g extract [21].…”
Section: Discussionmentioning
confidence: 98%
“…The Nrf2/ARE signaling pathway has been reported to be the key regulator response to oxidative stress, and a variety of natural products have been shown to promote the translocation of Nrf2 to the nucleus [ 21 ]. For example, damiana leaves extract was reported to protect against UVB-induced damage by regulating the AP-1 and Nrf2/ARE pathways in HaCaT cells [ 22 , 23 ]. To determine the antioxidant mechanisms activated by PASE, we analyzed the expression of antioxidant factors from the Nrf2/ARE signaling pathway in UVB-exposed HaCaT cells.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive reactive oxygen species are produced during skin photoaging. When the body cannot remove ROS in time, the redox system will be unbalanced, causing oxidative damage to intracellular nucleic acids, lipids and proteins, eventually triggering apoptosis and skin tissue damage ( Fitsiou et al, 2021 ; Kim et al, 2022 ). Therefore, it is imperative to use safe and effective phytochemicals to protect the skin from these harmful effects.…”
Section: Discussionmentioning
confidence: 99%